Immunohistochemical study on the endocrine cells in the pancreas of the ostrich (Struthio camelus) - Tarakcy, Berrin Gencer; Yaman, Mine; Bayrakdar, Ali (Medwell Online, 2007)
Insulin, glucagon and somatostatin immunoreactivity were found in ostrich pancreatic endocrine islet cells. Insulin immunoreactive cells were present in the central regions with high frequency. Glucagon immunoreactive cells were occurred in the peripheral regions with moderate frequency and a few of these cells were also demonstrated in the mantle regions. Somatostatin immunoreactive cells were detected in the mantle, peripheral and central regions with moderate frequency. In the exocrine pancreas, insulin, glucagon and somatostatin immunoreactivity were not detected. Gonadotropin Releasing Hormone (GnRH) immunoreactivity was not observed in the pancreatic endocrine and exocrine regions.
Keywords: insulin; glucagon; somatostatin; GnRH; ostrich; pancreas